2021
DOI: 10.3390/nu13020381
|View full text |Cite
|
Sign up to set email alerts
|

Deep Dive Into the Effects of Food Processing on Limiting Starch Digestibility and Lowering the Glycemic Response

Abstract: During processing of cereal-based food products, starch undergoes dramatic changes. The objective of this work was to evaluate the impact of food processing on the starch digestibility profile of cereal-based foods using advanced imaging techniques, and to determine the effect of preserving starch in its native, slowly digestible form on its in vivo metabolic fate. Four different food products using different processing technologies were evaluated: extruded products, rusks, soft-baked cakes, and rotary-molded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…These additional improvements may be impactful in a longer-term effect but have not been shown to interfere with acute metabolic response [16]. According to previous studies on cereal-based products, the control products induced a medium GI due to their content of SDS and fat [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These additional improvements may be impactful in a longer-term effect but have not been shown to interfere with acute metabolic response [16]. According to previous studies on cereal-based products, the control products induced a medium GI due to their content of SDS and fat [40].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been clearly shown for several years that food processes modify the starch structure configuration inside the food matrix depending on its level of gelatinization [16,39,41]. Several food processes used to make biscuits have been recently compared and showed that rotary molding technology which needs low water addition and smoother technological conditions is favorable to starch preservation in its native state by limiting starch gelatinization and maintaining a higher SDS content [40]. The originality of the present work is, that by using the same favorable technology (rotary molding), and by controlling some specific parts of the process, we were able to obtain a wide range of SDS, from 15 to 40% of available starch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These products were matched for the amount of available CHO by adapting products serving size to reach 50 g of available CHO for each. Products with the highest SDS content between 23.9 and 27.5 g/100 g induced the lowest glycemic responses, with the lowest incremental area under the curve (iAUC) 0–120 min of glucose and glycemic peak, associated with the lowest iAUC of insulin concentration [ 14 ]. A meta-analysis based on five studies using different SDS contents and matrices (SDS microspheres, pasta, breads, potatoes, biscuits, porridge) and culinary processes (boiling and cooling, rotary molding) over a single intake showed some discrepancies.…”
Section: Effects Of Slowly Digestible Starch and Resistant Starch On ...mentioning
confidence: 99%
“…An interesting study using several imaging techniques (X-ray diffraction, micro-X-ray microtomography, and electronic microscopy) evaluated four food products produced with different processing technologies (extruded products, rusks, soft-baked cakes, and rotary-molded biscuits). It was possible to observe that the rotary-molded process preserved the higher content of slowly digestible starch and its crystalline structure, thus resulting in a lower glycemic and insulinemic response [ 29 ].…”
Section: Introductionmentioning
confidence: 99%